Identity is a Fragmentary System - et. al., Nour Majid Ibrahim Hammad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Identity is one of the most important concepts dealt with in most recent studies, because it expresses the existence and belonging of the individual, and it is an integral part of his being, which he derives from the society to which he belongs. Identity is subjected to some difficulties and problems such as its fragmentation and tearing, and behind that stands several circumstances that led it to These conflicts, therefore, were the focus of attention of modern studies, and the novel has the largest share in this aspect in order to understand its importance, especially if it is related to the Arab identity based on Arabism, Islam and authenticity represented by customs, traditions, customs ... etc. The value of identity is evident in cultural studies that search for the texts of the text, uncover what is silent about it and what the discourse encircles in terms of the consistency of the context, and shed light on those cultural systems that have become fragmented in that identity and led to its fragmentation and tearing. For researchers and scholars to investigate its importance and its role in relying on the status of that identity and its specificity, and after that we stood on the procedural mulch to search for those cultural systems that have subsided behind the narrative texts in a way that is difficult to detect except through in-depth cultural reading.